(untitled) - Nielsen, Larry A. (Maryland, US., 1992)
Special Publication 23 Synthesis of current ways to tag and mark fish, crustaceans, and mollusks for later identification. Well-illustrated and suitable as a working manual or teaching text, the book gives the advantages, disadvantages, appropriate species, materials, procedures, and new developments for each class of tags and marks.
Keywords: Fish tagging,Animal marking,Fisheries; Research